Wild rain [large type] - Jenkins, Beverly, 1951- (Jenkins, Beverly, 1951- Women who dare, 2023)
"Banished by her grandfather at the age of eighteen, Spring Lee has survived scandal to claim her own little slice of Paradise, Wyoming. She's proud of working her ranch alone and unwilling to share it with a stranger - especially one like Garrett McCray, who makes her second-guess her resolve to avoid men. Garrett escaped slavery years ago and is now a reporter in Washington. He's traveled west to interview Dr. Colton Lee for an article, yet it's Lee's fearless sister, Spring, who captures his interest. Clad in denim and buckskins instead of dresses, she's the most fascinating woman he's ever met. And he's certain she also feels the connection that sizzles between them. But when a shadow from Spring's past returns, all is on the line: her ranch, her safety - and this wild, fierce love."--